Otoimmun Epilepsiler - Solmaz, İsmail and Konuşkan, Bahadır (Canpolat, Temel Pediatrik Epilepsi, 2024)
Epilepsi kronik bir hastalık olup, hastaların 1/3’ünde etyoloji net olarak aydınlatılamamıştır. Etyolojide saptanan sebepler dışlandıktan sonra anti nöbet ilaçlara yanıt alınamayan hastalarda otoimmun epilepsiler akla gelmelidir. Tanısal incelemelerde nörogörüntüleme ve elektroensefalografi yardımcı olmakla birlikte serolojik analizlerin tanısal değeri yüksektir. Tedavide anti nöbet ilaçların yanında erken dönemde immunsüpresif - immunmodülatuar tedavinin prognoza olumlu katkısı vardır. Epilepsy is a chronic disease and the etiology of epilepsy is not clearly elucidated in 1/3 of the patients. Autoimmune epilepsies should be considered in patients who do not respond to anti-seizure medications after exclusion of the causes found in the etiology. Although neuroimaging and electroencephalography are helpful in diagnostic investigations, serological analyses have a high diagnostic value. In addition to anti-seizure medications, early immunosuppressive-immunomodulatory treatment has a favourable contribution to the prognosis.